2015
DOI: 10.1007/s10144-015-0487-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive interference via display signals: the challenge of multiple receivers

Abstract: Sexually selected traits important in both mate and competitor recognition provide an opportunity to understand the tradeoffs associated with reproductive and competitive interference. When co-occurring species compete over similar resources, selection may promote signal similarity to facilitate competitive interactions in opposition to selection for signal divergence to maintain assortative mating. Bird song provides a classic example of contrasting selection on signal design, because songs function both in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Consequently, selective pressures are expected to promote divergence in species traits involved in species recognition, to reduce detrimental interactions, but only where they occur in sympatry. We do acknowledge that our survey sampled just one population per species, precluding the explicit analysis of the effect of sympatric congeners at the within-species level (Collyer & Adams, 2007;Wheatcroft, 2015). Nonetheless, our comparison of species within the ecologically homogeneous group of wall lizards revealed that the protein signal diverged more in those species pairs with higher geographic overlap.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, selective pressures are expected to promote divergence in species traits involved in species recognition, to reduce detrimental interactions, but only where they occur in sympatry. We do acknowledge that our survey sampled just one population per species, precluding the explicit analysis of the effect of sympatric congeners at the within-species level (Collyer & Adams, 2007;Wheatcroft, 2015). Nonetheless, our comparison of species within the ecologically homogeneous group of wall lizards revealed that the protein signal diverged more in those species pairs with higher geographic overlap.…”
Section: Discussionmentioning
confidence: 98%
“…Second, stricter song discrimination could result from divergence in genes underlying the perceptual system involved in song recognition (e.g., Haavie et al. ; Wheatcroft and Qvarnström ). For example, genetic variation across species underlies discrimination of conspecific song in nestling flycatchers (Wheatcroft and Qvarnström accepted).…”
Section: Discussionmentioning
confidence: 99%
“…A key prediction of this mechanism is that females from allopatric populations should discriminate against heterospecific songs. Second, if time in allopatry is insufficient, sympatry itself may promote stricter song discrimination either as a result of direct selection to avoid heterospecific songs to reduce mixed pairing (i.e., reinforcement; Hudson and Price 2014;Wheatcroft 2015), learning to avoid heterospecific songs due to costly behavioral interactions (Verzijden et al 2012b), or a byproduct of other evolutionary forces, such as ecological displacement (Pfennig and Pfennig 2009). In this case, only females from sympatric populations should discriminate against heterospecific songs.…”
mentioning
confidence: 99%
“…Females, on the other hand, can potentially reduce the costs of such pairings by extra‐pair mating with conspecific males (Svedin, Wiley, Veen, Gustafsson, & Qvarnström, 2008; Veen et al., 2001; but see also Knief, Bossu, & Wolf, 2020). As a result, in such systems, there may be particularly strong selection on male signalling traits, which should aid rapid divergence (Wheatcroft, 2015). Furthermore, whereas strong selection on females is likely to have substantial demographic effects, selection on males may little reduce population growth.…”
Section: Determinants Of the Speeds Of Extinction And Evolutionmentioning
confidence: 99%